2012
DOI: 10.1016/j.imbio.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Complement dysregulation and disease: From genes and proteins to diagnostics and drugs

Abstract: During the last decade, numerous studies have associated genetic variations in complement components and regulators with a number of chronic and infectious diseases. The functional characterization of these complement protein variants, in addition to recent structural advances in understanding of the assembly, activation and regulation of the AP C3 convertase, have provided important insights into the pathogenic mechanisms involved in some of these complement related disorders. This knowledge has identified po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 125 publications
1
87
0
1
Order By: Relevance
“…Subsequent functional analyses of various disease-associated genetic variants have demonstrated that complement dysregulation is a major contributor to pathogenesis in these disorders (42). These findings, in addition to the long-time realization that unwanted complement activation sustains the "vicious cycle" of inflammation and perpetuates tissue damage in many pathological conditions, have put complement inhibition in focus for development of new therapeutic agents (16).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent functional analyses of various disease-associated genetic variants have demonstrated that complement dysregulation is a major contributor to pathogenesis in these disorders (42). These findings, in addition to the long-time realization that unwanted complement activation sustains the "vicious cycle" of inflammation and perpetuates tissue damage in many pathological conditions, have put complement inhibition in focus for development of new therapeutic agents (16).…”
Section: Discussionmentioning
confidence: 99%
“…Misdirected or systemic, overwhelming activation leads to complement-associated diseases, such as age-related macular degeneration (AMD), atypical hemolytic uremic syndrome (aHUS), and C3 glomerulopathies, including C3 glomerulonephritis and dense deposit disease (DDD) (1)(2)(3)(4)(5). A number of complement inhibitors are being developed with the hope of applying them in the treatment of such diseases (6).…”
mentioning
confidence: 99%
“…FH-based therapeutics could be of advantage over certain current treatments, such as plasma infusion or eculizumab, which inhibits complement at a later step (5). Purified full-length FH showed efficacy in controlling the C3 convertase in a mouse model of FH deficiency (22) and in in vitro C3-deposition and cell-protection assays in the presence of aHUS-associated anti-FH autoantibodies or mutations in FH or C3 (23)(24)(25).…”
mentioning
confidence: 99%
“…The complement system can be activated by the classical, lectin, or alternative pathway. The C1r 3 protease is responsible for the first enzymatic events in the classical pathway of complement activation, through autoactivation and subsequent initiation of the cascade by cleaving and activating proenzyme C1s (2). The lectin pathway is activated by the MASP-1 and MASP-2 enzymes, whereas MASP-3, a splice variant of MASP-1, plays a presently less well characterized role in the system.…”
mentioning
confidence: 99%
“…The lectin pathway is activated by the MASP-1 and MASP-2 enzymes, whereas MASP-3, a splice variant of MASP-1, plays a presently less well characterized role in the system. The complement system is strongly implicated in many inflammatory disease states, and therefore inhibitors of the initiating proteases could be powerful anti-inflammatory agents (3). Understanding how C1r interacts with its target substrates is the key to the knowledge required to design effective inhibitors of complement activation by targeting this initiating enzyme.…”
mentioning
confidence: 99%